INCLUSION OF QUALITY STANDARD IN WATER PRICING POLICY - P. K. Gayen, S. Das (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The reform of water pricing structure is suggested on basis of water quality standard.It is noticed that performance of water treatment plant under authority is not satisfactory due to either lack of maintenance activity or lack of replacement/upgradation of old water treatment plant. In this context, this paper proposes rebate policy on water tax due to violation of quality up to certain limit. As a result, vigilant attitude of concerned administrative body is reflected on restoring standard quality of water to avoid loss of revenue.Thus, management on water treatment action is strengthened. As a result, clean i.e. hygienic water for water consumer can be assured via proposed pricing policy. Mathematical formulation of proposed tariff policy is also given in this paper.